Analisis Isi Pesan Dakwah Ustadz Hanan Attaki Tema “Suka Nunda Terus mau Sampai Kapan” Via Youtube - Muhammad Solihin; Akhmad Rifa’i; Robby Aditya Putra (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2022)
Da'wah is one of the most important parts of a Muslim's life. Of course, over time, da'wah activities on social media have not only become the style of preachers, but must be carried out. Likewise, Ustadz Hanan Attaki preaches through his YouTube channel which is gentle and pleasant to hear, as well as his speaking style which is very millennial friendly and easy for mad'u to understand, making him much-loved and sought after which later becomes the research material for this article. The purpose of this research is to get information about Ustadz Hanan Attaki's da'wah message on the topic Like to postpone until when do you want it on Hanan Attaki's Youtube channel. The researcher used a qualitative approach with a descriptive research type using the Holsti theory content analysis method. Primary data sources were obtained from data uploaded on Hanan Attaki's YouTube channel on September 3, 2022 and secondary data in the form of documents, books with the topics studied and with previous important studies as a comparison for this study. This research was conducted with several stages and data collection techniques in the form of observation and documentation. Research shows that; Ustadz Hanan Attaki's da'wah message includes not delaying good deeds, tips so as not to delay goodness, as well as God's promises to people who do the slightest good.